Reconciliation between heirs (exit) on estate division in inheritance: its provisions and forms in Islamic Jurisprudence - Muhammad Husni, Ahmad (International Organization of Scientific Research (IOSR), 2018)
Inheritance is of the most important branches of Islamic law, which every Muslim needs to know to understand his share in the estate left behind by the deceased in accordance with the Islamic law; it is regarded as one of the subject that has not been adequately researched on, in terms of both academic and law. Another most important part of inheritance in Islamic law is the issue of reconciliation between heirs on estate of inheritance to remove one or some of them from the division of the estate in exchange of something paid to him or them; it is of the issues needed by the heirs at all time to divide the estate between them, and to remove the one they do not need to remain with them when the subject matter is real estate, and things that may be affected if are divided based on the principles of inheritance. This issue is of the issues that do not get their adequate share of research; and those who wrote on inheritance among the contemporary scholars only discussed some of its forms and division; for this I wish to discuss this issue from the jurisprudential point of issue. This study adopts inductive and analytical approach to gather the views of scholars and researchers and their evidence and arguments on the matter, and texts related to it and to try to analyzethem to suit our contemporary reality. So, it is considered contracts that move ownership that must be studied by focusing on the pillars and conditions and the most important provisions which are distinct from the rest of contracts that move ownership.